Standard 6-week chemoradiation for elderly patients with newly diagnosed glioblastoma - Loïg Vaugier (Nature Portfolio, 2021)
Abstract Glioblastoma (GBM) is frequent in elderly patients, but their frailty provokes debate regarding optimal treatment in general, and the standard 6-week chemoradiation (CRT) in particular, although this is the mainstay for younger patients. All patients with newly diagnosed GBM and age ≥ 70 who were referred to our institution for 6-week CRT were reviewed from 2004 to 2018. MGMT status was not available for treatment decision at that time. The primary endpoint was overall survival (OS). Secondary outcomes were progression-free survival (PFS), early adverse neurological events without neurological progression ≤ 1 month after CRT and temozolomide hematologic toxicity assessed by CTCAE v5. 128 patients were included. The median age was 74.1 (IQR: 72–77). 15% of patients were ≥ 80 years. 62.5% and 37.5% of patients fulfilled the criteria for RPA class I–II and III–IV, respectively. 81% of patients received the entire CRT and 28% completed the maintenance temozolomide. With median follow-up of 11.7 months (IQR: 6.5–17.5), median OS was 11.7 months (CI 95%: 10–13 months). Median PFS was 9.5 months (CI 95%: 9–10.5 months). 8% of patients experienced grade ≥ 3 hematologic events. 52.5% of patients without neurological progression had early adverse neurological events. Post-operative neurological disabilities and age ≥ 80 were not associated with worsened outcomes. 6-week chemoradiation was feasible for “real-life” elderly patients diagnosed with glioblastoma, even in the case of post-operative neurological disabilities. Old does not necessarily mean worse.